552 A Single Centre Retrospective Study of Outcomes in Open Liver Surgery. (12th October 2021) - Shrestha, D; Gungadin, P; Sonanis, S; Sultana, A; Subar, D
Abstract: Aim: Despite advances in laparoscopic surgery for liver resections, an open approach remains the most frequent approach for complex liver resections for benign and malignant conditions. The aim of this study was to evaluate the clinical outcomes of patients undergoing open liver resections at a single tertiary HPB centre. Method: All patients undergoing open liver resections between March 2018-July 2020 were included. Clinical and pathological data was reviewed for all patients and data collected including demographics, indication for surgery, complications, length of hospital stay and 30- and 90-day mortality. Results: A total of 51 patients underwent open liver resection with median age of 65 (IQR 60.5-70.5). Indication for surgery included CRC metastasis (45%), HCC (27%), Intrahepatic cholangiocarcinoma (8%), Cholangiocarcinoma (8%), other metastasis (8%). The median hospital stay was 8 days (IQR 6-15). Complications were noted in 17 patients (Clavien-Dindo Classification III (8%) and IV (12 %). 6 patients had post op bile leaks, 4 with grade B and 2 with grade C bile leaks. 8 patients had post hepatectomy liver failure (5 Grade A, 2 Grade B, 3 Grade C). No mortality was noted at 30 and 90-day time-points. Conclusions: Our outcomes in terms of morbidity, mortality and hospital length of stay are similar to that in published literature.